2022
DOI: 10.3390/nu14204279
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Food Variety and Dietary Patterns Are Associated with Frailty among Chinese Older Adults: A Cohort Study Based on CLHLS from 2014 to 2018

Abstract: (1) Objective: To examine the association between posterior-derived dietary patterns, food variety, and frailty measured by frailty index (FI) in Chinese elderly. (2) Method: A cohort study based on the Chinese Longitudinal Healthy Longevity Survey (CLHLS) from 2014 to 2018 was conducted among older adults. The food variety was defined by the food variety score (FVS), which was calculated using the frequency of food categories consumption. Dietary patterns were obtained using factor analysis. A FI composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…After a critical review of titles and abstracts, 1301 articles were removed because they were unrelated to our research questions, and after a full-text review of the remaining 55 studies, the final 12 articles containing 25 available data met our inclusion criteria and were used in the systematic review (figure 1). 22 29–39…”
Section: Resultsmentioning
confidence: 99%
“…After a critical review of titles and abstracts, 1301 articles were removed because they were unrelated to our research questions, and after a full-text review of the remaining 55 studies, the final 12 articles containing 25 available data met our inclusion criteria and were used in the systematic review (figure 1). 22 29–39…”
Section: Resultsmentioning
confidence: 99%
“…In line with the ICFSR International Clinical Practice Guidelines, the daily habits of older adults, including nutritional practices, physical activity, and maintaining social connections, are crucial in effectively preventing frailty 5 . Regarding nutrition‐related factors, maintaining high food diversity with an adequate intake of proteins (such as meat and fish) and vegetables has been reported to reduce new‐onset frailty in older adults 23 . Moreover, it has been reported that high food diversity can reduce mortality risk in older adults with pre‐frailty and frailty, 24 and that a balanced diet is crucial for maintaining the physical health of older adults and preventing chronic diseases and complications due to malnutrition 25 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Regarding nutritionrelated factors, maintaining high food diversity with an adequate intake of proteins (such as meat and fish) and vegetables has been reported to reduce new-onset frailty in older adults. 23 Moreover, it has been reported that high food diversity can reduce mortality risk in older adults with pre-frailty and frailty, 24 and that a balanced diet is crucial for maintaining the physical health of older adults and preventing chronic diseases and complications due to malnutrition. 25 However, poor oral status has been reported to strongly predict new-onset frailty and mortality in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…This study applied the dietary variety score (DVS) to evaluate the initial dietary diversity in the 2008, 2011, 2014, and 2018 CLHLS surveys [18,29]. The intake frequency was used to indicate the intake status of food groups, including fresh fruit, vegetables, meat, fish, eggs, bean products, salted vegetables, sugar, garlic, milk products, nut products, mushrooms or algae, and tea.…”
Section: Dietary Variety Assessmentmentioning
confidence: 99%